Lactobacillus reuteri Surface Mucus Adhesins Upregulate Inflammatory Responses Through Interactions With Innate C-Type Lectin Receptors - Bene, Krisztián P.; Kavanaugh, Devon W.; Leclaire, Charlotte; Gunning, Allan P.; MacKenzie, Donald A.; Wittmann, Alexandra; Young, Ian D.; Kawasaki, Norihito; Rajnavolgyi, Eva; Juge, Nathalie (Frontiers in Microbiology, 2017)
The vertebrate gut symbiont Lactobacillus reuteri exhibits strain-specific adhesion and health-promoting properties. Here, we investigated the role of the mucus adhesins, CmbA and MUB upon interaction with the L. reuteri strains ATCC PTA 6475 and ATCC 53608 in human monocyte-derived DCs (moDCs). We showed that mucus adhesins increased the capacity of L. reuteri strains to interact with moDCs and promoted phagocytosis. Our data also suggest that mucus adhesins mediate anti- and pro-inflammatory effects by the induction of interleukin-10 (IL-10), tumor necrosis factor alpha (TNF-α), IL-1ß, IL-6, and IL-12 cytokines. L. reuteri ATCC PTA 6475 and ATCC 53608 strains were exclusively able to induce moDC-mediated Th1 and Th17 immune responses. We further showed that purified MUB activates moDCs and induces Th1 polarized immune responses associated with increased IFNγ production. MUB appeared to mediate these effects via binding to C-type lectin receptors (CLRs), as shown using cell reporter assays. Blocking moDCs with antibodies against dendritic cell-specific intercellular adhesion molecule 3-grabbing non-integrin (DC-SIGN) or Dectin-2 did not affect the uptake of the MUB-expressing strain, but reduced the production of TNF-α and IL-6 by moDCs significantly in line with the Th1 polarizing capacity of moDCs. The direct interaction between MUB and CLRs was further confirmed by force spectroscopy. Taken together these data suggest that mucus adhesins expressed at the cell surface of L. reuteri strains may exert immunoregulatory effects in the gut through modulating the Th1-promoting capacity of DCs upon interaction with C-type lectins.